Studi Literatur: Mengungkap Fraud – Red Flag, Fraud Evidence, dan Audit Digital - Retno Ayu Widyastuti; Tri Ratnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In an era of rapidly evolving digital transactions and the pervasive influence of technology in the financial world, fraud detection and prevention has become a key focus for companies, regulators, and auditors. This research aims to explore key concepts related to fraud, with an emphasis on red flags, evidence of fraud, and the transformative role of digital audit. The research method used a literature study, focusing on understanding and analyzing written sources relevant to the research topic without involving primary data collection. The results show that the integration of red flags in digital-based auditing is not just an application of technology, but also a proactive step to build a stronger layer of security to overcome fraud challenges in an ever-changing business environment. Continued efforts to develop and improve digital-based audit technology are expected to continue to provide benefits in identifying and preventing fraud, ensuring the sustainability of integrity and security in a dynamic business world.